Magnetoelectric magnetic field sensors. (November 2018) - Viehland, Dwight; Wuttig, Manfred; McCord, Jeffrey; Quandt, Eckhard
Abstract: Abstract : Highly sensitive magnetic field sensors using magnetoelectric (ME) bulk and thin-film composites consisting of magnetostrictive and piezoelectric phases are discussed. Examples include PZT (Pb(Zr x Ti1– x )O3 ) fibers and AlN as the piezoelectric component and amorphous magnetostrictive material, respectively, or their multilayers. Additionally, self-organized ME composites are discussed. These ME sensors offer a passive (consuming little to no power) nature, high sensitivities, large effect enhancements at mechanical resonances, and large linear dynamic ranges. At mechanical resonance, limits of detection in the fT/Hz 1/2 range can be achieved. Below the mechanical resonance frequency, the sensitivity can be enhanced through frequency conversion using alternating current magnetic or electric fields or by using magnetic field-induced changes of the elastic properties, the delta-E effect, where E represents Young's modulus. Noise floors of about 1–100 pT/Hz 1/2 at a frequency of f = 1 Hz can be obtained depending on the sensor size and the operational mode. For applications in unshielded environments, approaches to suppress acoustic and vibrational cross-sensitivities are presented.